Weight control practices of severely obese patients who are not seeking bariatric surgery. (5th July 2013) - Arterburn, David; Westbrook, Emily O.; Terrell, Andrew
<x xml:space="preserve">Abstract</x> Objective We sought to better understand why so few severely obese patients undergo bariatric surgery in the United States. Design and Methods We conducted a telephone survey to assess the weight control practices of severely obese patients who were not actively seeking bariatric surgery in Group Health, a health system in Washington State. Results Among 295 severely obese participants surveyed (63% response rate), most reported actively working on weight loss (58%), although current use of commercial weight loss programs (10%) and obesity pharmacotherapy (0.1%) was low. Household income and white race were strongly associated with lifetime use of commercial programs, suggesting a possible disparity in use of effective treatment for obesity. Many were interested in learning more about bariatric surgery (49%) and pharmacotherapy (53%), but few had ever discussed surgery (26%) or pharmacotherapy (33%) with their physician. Finally, although only 29% had coverage for bariatric surgery, those with coverage were not more likely to have discussed bariatric surgery with their physician. Conclusions Overall, our survey of severely obese patients who are not currently seeking bariatric surgery suggests that interest in obesity treatments is high, coverage and receipt of treatment is low, and that there is a potential socioeconomic disparity related to the use of commercial programs.